Mathematical models of collective dynamics and self-organization - Degond,P (2018)
In this paper, we begin by reviewing a certain number of mathematicalchallenges posed by the modelling of collective dynamics and self-organization.Then, we focus on two specific problems, first, the derivation of fluidequations from particle dynamics of collective motion and second, the study ofphase transitions and the stability of the associated equilibria.